Radiography of Trigeminal Neuralgia and Hemifacial Spasm - Sobel, David; Norman, David; Yorke, Craig H.; Newton, Thomas H. (American Journal of Neuroradiology, 1980)
Radiographic findings in 68 patients with trigeminal neuralgia and 24 patients with hemifacial spasm are reviewed. The relative value of various radiographic diagnostic procedures is discussed. Trigeminal neuralgia and hemifacial spasm are usually caused by vascular compression of the trigeminal root entry zone and facial nerve exit zone respectively. Computed tomography (CT) of the posterior fossa is the only radiographic screening procedure required. Angiography should be reserved for patients in whom CT findings suggest an aneurysm or tumor.